Developing Canva-Based Instructional Videos Through the ADDIE Model to Enhance Learning Outcomes - Ramadhani, Ramadhani; Efendi, Efendi; Afriani, Iim; Iskandar, M. Yakub (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Information and communication technology (ICT)-based learning media are increasingly expected to help elementary teachers present meaningful, multimodal, and learner-centred instruction. However, the practical availability of validated digital media for culture-related Pancasila Education remains limited in many elementary classrooms. This study developed and examined the feasibility of Canva-based instructional video media for fifth-grade students learning Indonesian cultural diversity. A research and development design was implemented using the ADDIE model: analysis, design, development, implementation, and evaluation. The participants were 25 fifth-grade students at State Elementary School 25 Sungai Sirah Hilir, Pesisir Selatan Regency. Data were collected using expert validation sheets, teacher and student practicality questionnaires, and pre-test and post-test learning outcome measures. The media was assessed by material, language, and media experts and then implemented in classroom learning. The overall expert validation reached 93.87%, indicating a very valid product. Practicality was also high, with the teacher response reaching 96.66% and the student response reaching 92.80%. Student learning outcomes improved from a pre-test mean of 66.20 (SD = 12.07) to a post-test mean of 85.20 (SD = 7.49), with classical mastery increasing from 24% to 88%. The paired-sample analysis showed a substantial improvement, t(24) = 8.57, p < .001, Cohen's dz = 1.71. These findings indicate that Canva-based video learning media developed through ADDIE is valid, practical, and educationally promising for supporting elementary students' learning outcomes in Pancasila Education.